High-entropy oxygen storage material and preparation method thereof

Through high entropy design, the YBCO oxygen storage material is modified, the element types are increased and the lattice distortion is induced, which solves the problem of poor thermal stability of YBCO materials, and improves the high temperature stability and oxygen exchange characteristics of the material.

CN119841278AActive Publication Date: 2025-04-18HUBEI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510004858.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-18
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The thermal stability of existing YBCO oxygen storage materials is poor, resulting in catalytic inactivation under high temperature conditions and the inability to effectively regulate automobile exhaust.

Method used

The YBCO material is modified through a high-entropy design, which increases the types of elements in the crystal structure, induces lattice distortion of the atomic configuration, and increases the configuration entropy, thereby improving the thermal stability and oxygen exchange characteristics of the material.

Benefits of technology

It significantly improves the thermal stability of the material, broadens the working temperature range, maintains good oxygen storage performance under high temperature conditions, and extends the working life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841278A_ABST
    Figure CN119841278A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy oxygen storage material and a preparation method thereof, and belongs to the technical field of oxygen storage materials. The molecular formula of the high-entropy oxygen storage material is YBaCo (4-n) XnO7 + delta, and delta is oxygen adsorption molar weight, 0 lt; delta < = 1.5; x is at least five of Cu, Fe, Zn, Ga, Al and Mn; n is the doping amount of the X metal element, 0 lt; n < = 1. The preparation method of the high-entropy oxygen storage material comprises a solid-phase reaction method, a sol-gel method or an electrostatic spinning method. The oxygen storage material is subjected to high-entropy modification based on YBaCo4O7 + delta oxide, the synergistic effect among multiple sites is exerted through selection of doped metal elements and regulation and control of the content, the thermal stability of the material is remarkably improved, and the working temperature window of the material is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oxygen storage materials, and in particular to a high entropy oxygen storage material and a preparation method thereof. Background Art

[0002] As an important component of automobile exhaust treatment catalysts, oxygen storage materials should have reversible oxygen storage / release functions to dynamically regulate and buffer automobile exhaust, thereby maintaining the air-fuel ratio near the theoretical value. In order to improve the working life of oxygen storage materials in automobile exhaust catalytic conversion applications and their stability under specific working conditions, it is of great significance to optimize and improve the phase structure stability and temperature operation window of oxygen storage materials themselves. 7+δ (YBCO) oxide is a widely studied oxygen storage material, but its operating temperature range is narrow. When the temperature is higher than 500°C, the YBCO phase will decompose, resulting in catalytic deactivation of the automobile exhaust treatment system. In response to the above problems, based on detailed research and material optimization, high entropy modification was finally selected to improve the thermal stability of the YBCO material and inhibit its component segregation and phase separation.

[0003] Based on high entropy design, YBCO is optimized and modified to obtain high entropy YBCO material (high-entropyYBCO, HE-YBCO). The essence of high entropy design is to increase the types of elements in the crystal structure, induce lattice distortion of atomic configuration, and thus increase the entropy driven by distortion in the system, i.e., configuration entropy S conf The value increases. It is known that Gibbs free energy G = H-TS, where H is enthalpy, T is absolute temperature, and S is entropy. If the configuration entropy S conf (a component of S) increases, the Gibbs free energy decreases, the thermodynamic stability of the system increases, and the phase structure stability of the material will be improved on a macroscopic level. In order to obtain high performance, it is necessary to introduce highly reactive transition metal elements, while to ensure stability, it is necessary to introduce less reactive elements to enhance the strength of the cation-oxygen bond. High entropy oxygen storage materials can effectively protect the segregation induced by the diffusion of elements of other components of the device to its surface due to their high thermodynamic stability driven by high configurational entropy. In addition, they can effectively improve the oxygen vacancy concentration and oxygen surface exchange characteristics. There are unique interactions between adjacent atoms of different elements. High entropy oxygen storage materials can provide a large number of unique surface binding sites. The selection and proportion of doping and substitution elements directly affect the number and local composition of reactive sites, thereby optimizing the oxygen storage characteristics of the material. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present invention provides a high entropy oxygen storage material and a preparation method thereof, aiming to solve the technical problem of poor thermal stability of the existing YBCO material.

[0005] In the first aspect, the present invention provides a high entropy oxygen storage material having YBaCo (4-n) X n O 7+δ The molecular formula is, wherein δ is the oxygen adsorption molar amount, 0<δ≤1.5; X is at least five of Cu, Fe, Zn, Ga, Al, and Mn; n is the doping amount of the metal element, 0 <n≤1。

[0006] YBaCo4O7 is a new type of perovskite-like compound. Because it has the non-stoichiometric properties unique to perovskite-like materials, it can release and absorb oxygen atoms (1.5 oxygen atoms are adsorbed per unit cell) when the ambient atmosphere or temperature changes, so the molecular formula is often written as YBaCo4O 7+δ , the value of oxygen adsorption molar amount δ varies from 0 to 1.5.

[0007] The above high entropy oxygen storage material YBaCo (4-n) X n O 7+δ In the above formula, X is a doped metal element. 7+δ Doping can improve the high temperature stability of the material.

[0008] Preferably, the X metal element includes four metal elements of Ga, Fe, Zn, Cu, and at least one of Al and Mn.

[0009] Preferably, the molar amount of each metal element in the X metal element is equal.

[0010] In a second aspect, the present invention provides a method for preparing a high entropy oxygen storage material, comprising the following steps: mixing an yttrium source, a barium source, a cobalt source and a doped metal element source to prepare a high entropy oxygen storage material; The preparation method includes any one of a solid phase reaction method, a sol-gel method, and an electrostatic spinning method; The yttrium source includes a metal oxide or a soluble salt of yttrium; The barium source includes a metal oxide or a soluble salt of barium; The cobalt source includes metal oxides or soluble salts of cobalt; The doping metal element source includes a metal oxide or a soluble salt of the doping metal element.

[0011] Preferably, the solid phase reaction method specifically comprises: According to the stoichiometric ratio, the yttrium source, the barium source, the cobalt source and the doped metal element source are fully mixed with ethanol and calcined once, and then ground, pressed into tablets and calcined twice in sequence to obtain the high entropy oxygen storage material.

[0012] In the present invention, the valence of the metal element in the metal oxide does not affect the preparation of the material. For example, when a high entropy oxygen storage material containing the Cu element needs to be prepared, either copper oxide or cuprous oxide can be used.

[0013] Preferably, the primary calcination temperature is 800-1200°C, the secondary calcination temperature is 1000-1500°C, and the secondary calcination temperature is higher than the primary calcination temperature. The secondary calcination temperature is higher than the primary calcination temperature to ensure sufficient densification of the material and stability of the crystal phase, thereby obtaining a high entropy oxygen storage material with excellent performance.

[0014] Preferably, the sol-gel method specifically includes: According to the stoichiometric ratio, the yttrium source, barium source, cobalt source, doping metal element source, stabilizer and chelating agent are dissolved in water, heated to form a gel, the gel is dried to form a precursor, ground and sintered to obtain the high entropy oxygen storage material.

[0015] Preferably, the stabilizer comprises ethylene glycol, and the chelating agent comprises glycine and / or citric acid.

[0016] Preferably, the heating temperature is 150-400°C, and the sintering temperature is 1000-1200°C.

[0017] Preferably, the electrospinning method specifically comprises: According to the stoichiometric ratio, the yttrium source, barium source, cobalt source and doped metal element source, stabilizer and chelating agent are dissolved in water, a polyvinyl pyrrolidone solution is added and stirred to obtain a precursor solution, the precursor solution is jet-spun in an electric field to obtain a precursor fiber, and the high entropy oxygen storage material is obtained after drying and heat treatment.

[0018] Preferably, the stabilizer includes ethylene glycol, the chelating agent includes citric acid; the voltage of the electric field is 10-15V, the injection rate of the precursor solution is 0.1-0.5mL / h, and the heat treatment temperature is 800-1200°C.

[0019] The present invention is based on the doping tolerance principle of substitutional solid solution. The closer the atomic size, electronegativity and valence state are, the greater the solid solubility. Therefore, through screening and measurement, the elements Cu, Fe, Zn, Ga, Al and Mn are determined to be explored in order to obtain a single-phase high-entropy structure oxygen storage material.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a high entropy oxygen storage material having YBaCo (4-n) X n O 7+δThe present invention is carried out by YBaCo4O 7+δ Metal doping is performed to increase the types of elements in the crystal structure, inducing lattice distortion of the atomic configuration, thereby increasing the distortion-driven entropy in the system, i.e., the configuration entropy S conf The value increases, and a high entropy oxygen storage material is obtained. The oxygen storage material is based on YBaCo4O 7+δ The oxide is modified by high entropy, and the synergistic effect between multiple sites is exerted by selecting the doped metal and regulating the content, which significantly improves the thermal stability of the material and broadens its operating temperature range. The test results show that it still has good oxygen storage performance under high temperature conditions. The preparation method of the high entropy oxygen storage material provided by the present invention is simple, and the high entropy oxygen storage material of the present invention can be obtained by solid phase reaction method, glycine complex decomposition method, sol-gel method or electrostatic spinning method, which is convenient for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The high entropy oxygen storage material sample prepared in Example 1 and its XRD spectrum after being kept at 600° C. in air for 10 h; Figure 2 The high entropy oxygen storage material sample prepared in Example 2 and its XRD spectrum after being kept at 600° C. in air for 10 h; Figure 3 The high entropy oxygen storage material sample prepared in Comparative Example 1 and its XRD spectrum after being kept at 600°C in air for 10 hours; Figure 4 The high entropy oxygen storage material sample prepared in Comparative Example 2 and its XRD spectrum after being kept at 600°C in air for 10 hours; Figure 5 The oxygen storage material sample prepared in Comparative Example 3 and its XRD spectrum after being kept at 600°C in air for 10 hours; Figure 6 This is a diagram showing the oxygen storage performance of the high entropy oxygen storage material sample prepared in Example 1 at 350°C. DETAILED DESCRIPTION

[0022] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0023] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0024] 1. Preparation method Example 1 Preparation of high entropy oxygen storage material powder by sol-gel method YBaCo3Ga 0.2 Al 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ The preparation method comprises the following steps: (1) Weigh the metal nitrates Y(NO3)3, Ba(NO3)2, Co(NO3)2, Ga(NO3)3, Al(NO3)3, Fe(NO3)3, Zn(NO3)2, and Cu(NO3)2 in a molar ratio of 1:1:3:0.2:0.2:0.2:0.2, dissolve the metal nitrates in deionized water, and add ethylene glycol and citric acid as chelating agents. The molar ratio of the total metal ions, ethylene glycol, and citric acid is 1:1:1.5. After stirring evenly, slowly add ammonia water to adjust the pH value to 7; (2) The solution was heated and stirred at 120 °C until it reached a gel state. Subsequently, the gel was dried at 350 °C for 4 h to obtain a porous precursor. After the precursor was ground into powder, it was heated to 1000 °C in air at a heating rate of 5 °C / min and sintered for 2 h. Finally, it was naturally cooled to room temperature to obtain a high entropy oxygen storage material powder.

[0025] It has been verified that the molecular formula of the obtained high entropy oxygen storage material is YBaCo3Ga 0.2 Al 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ .

[0026] Example 2 Synthesis of high entropy oxygen storage material powder by sol-gel method YBaCo3Ga 0.2 Mn 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ The preparation method comprises the following steps: (1) Weigh metal nitrates Y(NO3)3, Ba(NO3)2, Co(NO3)2, Ga(NO3)3, Mn(NO3)2, Fe(NO3)3, Zn(NO3)2, and Cu(NO3)2 in a molar ratio of 1:1:3:0.2:0.2:0.2:0.2, dissolve the metal nitrates in 0.2 mol / L glycine solution, and stir at 40°C to form a uniform solution; (2) Ethylene glycol (EG) was added to the solution to form a metal-glycine complex through a chelation process, and the obtained transparent red solution was stirred at 100 °C for 3 h to obtain a gel, which was then pyrolyzed at 150 °C in air for 3.5 h to form a black honeycomb precursor; (3) After the precursor is ground into powder, the temperature is increased to 1050°C at a rate of 3°C / min in air and sintered for 4 h. Finally, the powder is naturally cooled to room temperature to obtain a high entropy oxygen storage material powder.

[0027] It has been verified that the molecular formula of the obtained high entropy oxygen storage material is YBaCo3Ga 0.2 Mn 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ .

[0028] Example 3 Synthesis of high entropy oxygen storage material powder by sol-gel method YBCo 3.5 Ga 0.1 Al 0.1 Fe 0.1 Zn 0.1 Cu 0.1 O 7+δ The preparation method comprises the following steps: (1) Weigh metal nitrates Y(NO3)3, Ba(NO3)2, Co(NO3)2, Ga(NO3)3, Al(NO3)3, Fe(NO3)3, Zn(NO3)2, and Cu(NO3)2 in a molar ratio of 1:1:3.5:0.1:0.1:0.1:0.1, dissolve the metal nitrates in deionized water, and add ethylene glycol and citric acid as chelating agents. The molar ratio of the total metal ions, ethylene glycol, and citric acid is 1:1:1.5. Stir well and slowly add ammonia water to adjust the pH value to 7; (2) The solution was heated and stirred at 120 °C until it reached a gel state. Subsequently, the gel was dried at 350 °C for 4 h to obtain a porous precursor. After the precursor was ground into powder, it was heated to 1000 °C in air at a heating rate of 5 °C / min and sintered for 2 h. Finally, it was naturally cooled to room temperature to obtain a high entropy oxygen storage material powder.

[0029] It has been verified that the molecular formula of the obtained high entropy oxygen storage material is YBaCo 3.5 Ga 0.1 Al 0.1 Fe 0.1 Zn 0.1 Cu 0.1 O 7+δ .

[0030] Example 4 Synthesis of high entropy oxygen storage material powder by solid phase reaction YBaCo3Ga 0.2 Al 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ The preparation method comprises the following steps: (1) Weighing metal oxides Y2O3, BaO, CoO, Ga2O3, Al2O3, FeO, ZnO, and CuO in a molar ratio of 0.5:1:3:0.1:0.1:0.2:0.2, mixing with ball mill beads and ethanol in a ball mill (500 r / min, 10 h), then filtering the obtained mortar-like product and drying it into a powder sample, calcining it once in air at 1000°C for 12 h, and granulating it to improve the morphology of the metal oxides; (2) The sample after the first calcination was ground and pressed into sheets, and then calcined for a second time at 1200°C for 24 h to achieve a solid-phase reaction. After naturally cooling to room temperature, the high-entropy oxygen storage material powder was obtained by grinding and ball milling.

[0031] It has been verified that the molecular formula of the obtained high entropy oxygen storage material is YBaCo3Ga 0.2 Al 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ .

[0032] Example 5 Preparation of high entropy oxygen storage material nanofibers by electrospinning YBaCo3Ga 0.2 Al 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ The preparation method comprises the following steps: (1) Weigh the metal nitrates Y(NO3)3, Ba(NO3)2, Co(NO3)2, Ga(NO3)3, Al(NO3)3, Fe(NO3)3, Zn(NO3)2, and Cu(NO3)2 in a molar ratio of 1:1:3:0.2:0.2:0.2:0.2, dissolve the metal nitrates in deionized water, and the water content in the solution is 70% (mass fraction, the same below), then add an aqueous solution of citric acid and ethylene glycol (adjust the pH of the aqueous solution of citric acid and ethylene glycol to 5 with ammonia water, and the water content in the solution is 58%), stir and mix evenly, and the molar ratio of the total metal ions, citric acid, and ethylene glycol is 1:2:3; The solution was placed in a water bath at 80°C and stirred for 5 hours to obtain a sol. Polyvinyl pyrrolidone (PVP, molecular weight 1300000) was first dissolved in deionized water to prepare a PVP aqueous solution with a mass fraction of 15%. A certain amount of PVP aqueous solution was then added to the sol and magnetically stirred for 10 hours to obtain a precursor solution with a PVP content of 3%. The precursor solution was injected into a syringe with a stainless steel needle (diameter 0.8 mm) and installed on a syringe pump. The electrospinning voltage was set to 12 kV, the distance between the needle and the collector was 10 cm, and the supply rate of the precursor solution was 0.3 mL / h. The precursor fiber thus obtained was dried and heat treated at 1000°C for 2 hours to obtain high entropy oxygen storage material nanofibers. It has been verified that the molecular formula of the obtained high entropy oxygen storage material is YBaCo3Ga 0.2 Al 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ .

[0033] Comparative Example 1 This comparative example adopts the preparation method of Example 1, and the preparation steps are the same as those of Example 1. The difference between this comparative example and Example 1 is that the molar ratio of the metal nitrates Y(NO3)3, Ba(NO3)2, and Co(NO3)2 is 1:1:4 during the preparation; it is verified that the molecular formula of the obtained high entropy oxygen storage material is YBaCo4O 7+δ .

[0034] Comparative Example 2 This comparative example adopts the preparation method of Example 1, and the preparation steps are the same as those of Example 1. The difference between this comparative example and Example 1 is that in this example, the molar ratio of the metal nitrates Y(NO3)3, Ba(NO3)2, Co(NO3)2, Ga(NO3)3, Ni(NO3)2, Fe(NO3)3, Zn(NO3)2, and Cu(NO3)2 is 1:1:3:0.2:0.2:0.2:0.2:0.2, and the target desired high entropy oxygen storage material YBaCo3Ga 0.2 Ni 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ , but X-ray diffractometer (XRD) characterization (such as Figure 4 ) shows that when Ni is doped, impurity peaks appear and a uniform oxide solid solution is not formed, indicating that the Ni element is not successfully doped into the YBCO lattice, but is mixed in the powder product in the form of NiO.

[0035] Comparative Example 3 This comparative example adopts the preparation method of Example 1, and the preparation steps are the same as those of Example 1. The difference between this comparative example and Example 1 is that: during the preparation, the molar ratio of the metal nitrates Y(NO3)3, Ba(NO3)2, Co(NO3)2, Ga(NO3)3, Sc(NO3)3, Fe(NO3)3, Zn(NO3)2, and Cu(NO3)2 is 1:1:3:0.2:0.2:0.2:0.2:0.2; the molecular formula of the target high entropy oxygen storage material is YBaCo3Ga 0.2 Sc 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ , but X-ray diffractometer (XRD) characterization (such as Figure 5 (as shown in the figure) shows that when Sc is doped, there are impurity peaks, and no uniform oxide solid solution is formed, indicating that the Sc element is not successfully doped into the YBCO lattice but is mixed in the powder product in the form of Sc2O3.

[0036] 2. Test Method (1) Thermal stability test of high entropy oxygen storage materials Thermal stability tests were performed on the oxygen storage material samples prepared in Examples 1-2 and Comparative Example 1, and the oxygen storage material samples and the samples after being kept at 600° C. in air for 10 h were characterized using an X-ray diffractometer.

[0037] (2) Oxygen storage performance test of high entropy oxygen storage materials The oxygen storage material samples prepared in Examples 1 to 5 were subjected to an oxygen absorption / desorption cycle performance test at 350°C. The test conditions were as follows: the samples were heated to 350°C in a pure nitrogen atmosphere and kept at a constant temperature. After the readings stabilized, the atmosphere was switched to pure oxygen. The samples adsorbed oxygen until the peak value was reached, and then the samples were switched to pure nitrogen for desorption.

[0038] III. Analysis of test results of various embodiments and comparative examples (1) Analysis of thermal stability test results of high entropy oxygen storage materials Figure 1 The XRD pattern of the sample in Example 1 and its XRD pattern after being kept at 600°C in air for 10 hours; Figure 2 The XRD pattern of the sample in Example 2 and its XRD pattern after being kept at 600°C in air for 10 hours; Figure 3 The XRD spectrum of the sample in comparative example 1 and its XRD spectrum after being kept at 600°C in air for 10 hours; it has been verified that the XRD spectra of the high entropy oxygen storage materials prepared in Examples 1~2 of the present invention all show good peak shapes after being kept at 600°C in air for 10 hours, while the structure of the material in comparative example 1 is destroyed after being kept at 600°C in air for 10 hours, indicating that the high entropy oxygen storage material structure prepared in the examples of the present invention has good thermal stability.

[0039] (2) Analysis of test results of oxygen storage performance of high entropy oxygen storage materials The test results of oxygen storage performance of high entropy oxygen storage materials are shown in Table 1.

[0040] Table 1

[0041] The results in Table 1 show that the high entropy oxygen storage material prepared in the present invention has good oxygen storage performance under high temperature conditions.

[0042] Figure 6 The high entropy oxygen storage material YBaCo3Ga prepared in Example 1 0.2 Al 0.2 Fe 0.2 Zn 0.2 Cu 0.2 O 7+δ The oxygen absorption / desorption cycle performance test spectrum of the sample at 350°C shows that within three oxygen absorption / desorption cycles, the sample exhibits highly reversible oxygen absorption / desorption behavior.

[0043] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present invention.

Claims

1. A high entropy oxygen storage material, characterized in that: The molecular formula of this high entropy oxygen storage material is YBaCo (4-n) X n O 7+δ , where δ is the oxygen adsorption molar amount, 0<δ≤1.5; X is at least five of Cu, Fe, Zn, Ga, Al, and Mn; n is the doping amount of the X metal element, 0 <n≤1。 2. A high entropy oxygen storage material according to claim 1, characterized in that: The X metal element includes four metal elements of Ga, Fe, Zn, Cu, and at least one of Al and Mn.

3. A high entropy oxygen storage material according to claim 1, characterized in that: The molar amount of each metal element in the X metal elements is equal.

4. A method for preparing a high entropy oxygen storage material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: A high entropy oxygen storage material is prepared by mixing a yttrium source, a barium source, a cobalt source and a doped metal element source; The preparation method includes any one of a solid phase reaction method, a sol-gel method, and an electrostatic spinning method; The yttrium source includes a metal oxide or a soluble salt of yttrium; The barium source includes a metal oxide or a soluble salt of barium; The cobalt source includes metal oxides or soluble salts of cobalt; The doping metal element source includes a metal oxide or a soluble salt of the doping metal element.

5. The method for preparing a high entropy oxygen storage material according to claim 4, characterized in that: The solid phase reaction method specifically comprises: According to the stoichiometric ratio, the yttrium source, the barium source, the cobalt source and the doped metal element source are fully mixed with ethanol and calcined once, and then ground, pressed into tablets and calcined twice in sequence to obtain the high entropy oxygen storage material.

6. The method for preparing a high entropy oxygen storage material according to claim 5, characterized in that: The primary calcination temperature is 800-1200° C., the secondary calcination temperature is 1000-1500° C., and the secondary calcination temperature is higher than the primary calcination temperature.

7. The method for preparing a high entropy oxygen storage material according to claim 4, characterized in that: The sol-gel method specifically comprises: According to the stoichiometric ratio, the yttrium source, barium source, cobalt source, doping metal element source, stabilizer and chelating agent are dissolved in water, heated to form a gel, the gel is dried to form a precursor, ground and sintered to obtain the high entropy oxygen storage material.

8. The method for preparing a high entropy oxygen storage material according to claim 7, characterized in that: The stabilizer includes ethylene glycol, and the chelating agent includes glycine and / or citric acid; the heating temperature is 150-400°C, and the sintering temperature is 1000-1200°C.

9. The method for preparing a high entropy oxygen storage material according to claim 4, characterized in that: The electrospinning method specifically comprises: According to the stoichiometric ratio, the yttrium source, barium source, cobalt source and doped metal element source, stabilizer and chelating agent are dissolved in water, a polyvinyl pyrrolidone solution is added and stirred to obtain a precursor solution, the precursor solution is jet-spun in an electric field to obtain a precursor fiber, and the high entropy oxygen storage material is obtained after drying and heat treatment.

10. The method for preparing a high entropy oxygen storage material according to claim 9, characterized in that: The stabilizer includes ethylene glycol, and the chelating agent includes citric acid; the voltage of the electric field is 10-15V, the injection rate of the precursor solution is 0.1-0.5mL / h, and the heat treatment temperature is 800-1200°C.

Citation Information

Patent Citations

  • Mixed conductor oxide oxygen-storage material and preparation method and application thereof

    CN104549312A

  • System and method for preparing oxygen from medium / low-temperature waste heat

    CN105110299A

  • Positive electrode catalyst for metal-air battery and metal-air battery

    JP2018152298A

  • Polymer-assisted deposition of films

    US20050043184A1